Antibacterial Activities and Toxicity of Streptosporangium sp. SM1P - Risa Nofiani; Rizky Rizky; Ridho Brilliantoro (Molekul, 2021)
This study aims to explore the anti-bacterial and toxicity activities from a rare actinobacterium isolated from mangrove, Mempawah District, West Kalimantan. The mangrove mud sample from Mempawah district was inoculated on ISP4 agar using a pour plate method. After 4 days of incubation, a colony of suspected actinobacterium was appeared, then isolated and coded as SM1P. SM1P was characterized based on morphological and biochemical traits and identified as a genus of Streptroporangium then called Streptroporangium sp. SM1P. Streptroporangium sp. SM1P was carried out anti-bacterial assay on both ISP1 agar and ISP4 agar media using the cross-streak method for the solid-state fermentation. The result showed that Streptroporangium sp. SM1P could inhibit Streptococcus sp. and Salmonella typhi on ISP1 agar and treptococcus sp., Escherichia coli, Vibrio cholerae, Staphylococcus aureus and Salmonella typhi on ISP4 agar.  Streptroporangium sp. SM1P was cultivated on ISP1 broth and extracted using ethyl acetate, then evaporated to obtain crude extract. The crude extract was used for anti-bacterial assay (well-diffusion method for liquid-state fermentation) and toxicity assay (brine shrimp lethality test). The crude extract was active against 2 of the test bacteria (Streptococcus sp. and E. coli). The best medium and state fermentation for anti-bacterial assay were ISP4 agar with the condition of solid-state fermentation. The extract SM1P prepared on ISP1 broth showed toxic activity based on LC50 (106.094 µg/mL). Therefore, Streptroporangium sp. SM1P have a potential source to explore secondary metabolites having anti-bacterial and toxicity activities.